Removal efficacy of various calcium hydroxide/chlorhexidine medicaments from the root canal with the aid of biological microscope - Ankush Jasrotia; Riyaz Farooq; Ravinder Kumar Bhagat; Kanchan Bhagat; Nidhi Sharma; Sheikh Tafazul Habib (Wolters Kluwer Medknow Publications, 2019)
Aim: An in vitro study was conducted to comparatively evaluate the two techniques - hand instrumentation and ultrasonic file irrigation for removal of various calcium hydroxide (Ca[OH]2)/chlorhexidine containing medicaments from the root canal by using Biological microscope and Digital Camera. Materials and Methods: Sixty-four human single-rooted teeth with straight canals were used. Root canal preparation was performed using Pro-taper Universal for Hand use (Dentsply Maillefer, Ballaigues Switzerland). Teeth were randomly divided into three Groups A, B, and C of 21 teeth each, the remaining tooth remained untouched and served as a negative control. Teeth of Group A were filled with Ca(OH)2 mixed with saline. Teeth of Group B were filled with Ca(OH)2 mixed with 0.2% chlorhexidine gel. Teeth of Group C were filled with Ca(OH)2 mixed with 0.12% chlorhexidine solution. Teeth were stored at 37°C and 100% relative humidity for 7 days. Then Ca(OH)2 was removed using two techniques: hand instrumentation and ultrasonic file irrigation in both groups. Teeth were sectioned longitudinally and observed under Biological microscope and Digital Camera. Results were statistically analyzed with the Mann-Whitney and Kruskal-Wallis test. Results: The results showed a significant difference between hand instrumentation and ultrasonic file irrigation in cervical and middle third, but no statistic difference in apical third. Conclusion: None of the techniques used in this study removed the inter-appointment root canal medicaments completely.